The role of mitochondria in the ischemic-reperfusion damage of the brain in operations on aortal arch in conditions of experiment - S. M. Gramatiuk; Yu. V. Ivanova; V. I. Kravchenko; O. O. Lohvinenko (Клінічна хірургія, 2020)
Objective. To investigate in experiment a functional state of mitochondria from the brain cells after its acute ischemic injury and processes, which take place in the brain in conditions of experimental ischemia/reperfusion; to analyze a correlation of the states investigated with the ischemic-reperfusion changes in the brain of patients, having the aortal arch aneurism, operated in environment of hypothermia and artificial cerebral perfusion.